2022
DOI: 10.3390/microorganisms10081672
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gut Microbiome Diversity and Composition and Heat Tolerance in Cattle

Abstract: Cattle are raised around the world and are frequently exposed to heat stress, whether in tropical countries or in regions with temperate climates. It is universally acknowledged that compared to those in temperate areas, the cattle breeds developed in tropical and subtropical areas have better heat tolerance. However, the underlying mechanism of heat tolerance has not been fully studied, especially from the perspective of intestinal microbiomics. The present study collected fecal samples of cattle from four re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Second, functional genes associated with carbohydrate metabolism were enhanced in P. przewalskii , conforming to the metabolic cold adaption hypothesis which predicts an increase in the metabolic rate of ectotherms from cold environments compared with their more temperate counterparts ( Clarke, 2003 ; Schaefer and Walters, 2010 ). In a recent study on two Phrynocephalus lizards occurring in thermally different regions, Chen et al (2022) found that the gut microbiota had a higher abundance of functional categories associated with metabolism in a high-altitude species ( Phrynocephalus erythrurus ) occurring from 4,500 to 5,300 m than in a low-altitude species ( P. przewalskii ) occurring from 500 to 1,700 m. Here, we found that, as in cattle where Firmicutes assimilate nutrients more efficiently in warm tropical environments ( Zhang et al, 2022 ), the relative abundance of Firmicutes in the small-intestinal microbiota was higher in the warm-climate species than in the cold-climate species. Firmicutes are more efficient in dietary caloric intake than Bacteroidetes ( Turnbaugh et al, 2006 ; Krajmalnik-Brown et al, 2012 ; Semova et al, 2012 ), and short-chain fatty acids produced by Firmicutes can be directly absorbed by the host as an energy source to promote mass gain ( den Besten et al, 2013 ).…”
Section: Discussionsupporting
confidence: 50%
“…Second, functional genes associated with carbohydrate metabolism were enhanced in P. przewalskii , conforming to the metabolic cold adaption hypothesis which predicts an increase in the metabolic rate of ectotherms from cold environments compared with their more temperate counterparts ( Clarke, 2003 ; Schaefer and Walters, 2010 ). In a recent study on two Phrynocephalus lizards occurring in thermally different regions, Chen et al (2022) found that the gut microbiota had a higher abundance of functional categories associated with metabolism in a high-altitude species ( Phrynocephalus erythrurus ) occurring from 4,500 to 5,300 m than in a low-altitude species ( P. przewalskii ) occurring from 500 to 1,700 m. Here, we found that, as in cattle where Firmicutes assimilate nutrients more efficiently in warm tropical environments ( Zhang et al, 2022 ), the relative abundance of Firmicutes in the small-intestinal microbiota was higher in the warm-climate species than in the cold-climate species. Firmicutes are more efficient in dietary caloric intake than Bacteroidetes ( Turnbaugh et al, 2006 ; Krajmalnik-Brown et al, 2012 ; Semova et al, 2012 ), and short-chain fatty acids produced by Firmicutes can be directly absorbed by the host as an energy source to promote mass gain ( den Besten et al, 2013 ).…”
Section: Discussionsupporting
confidence: 50%
“…The relative abundance of Euryarchaeota was lower in individuals with high ATP enzyme activity and MDA contents, and the relative abundance of Methanobrevibacter was lower in individuals with a high MDA content. Euryarchaeota represents a major branch of methane-producing archaea capable of converting acetates, methanol, and methylamines within the intestinal tract into methane [52,53], simultaneously generating ATP [54].…”
Section: Discussionmentioning
confidence: 99%
“…Dairy calves used in the study were transported to the university site in two different batches, the first batch was received in mid-Spring and the second batch in late-Summer. In previous studies, it has been shown that environmental temperature can cause heat stress that then affects the intestinal bacterial community [ 27 , 28 ]. In addition, the difference between batches could be explained by the inherit variation that occurs between animals.…”
Section: Discussionmentioning
confidence: 99%